Google Workspace user guide - Iyer, Balaji (Packt Publishing, 2022)
Explore the suite of apps that enhance productivity and promote efficient collaboration in your business Key Features Set up your own project in Google Workspace and improve your ability to interact with different services Understand how a combination of options can help businesses audit their data to be highly secure Deploy Google Workspace, configure users, and migrate data using Google Workspace Book Description Google Workspace has evolved from individual Google services to a suite of apps that improve productivity and promote efficient collaboration in an enterprise organization. This book takes you through the evolution of Google Workspace, features included in each Workspace edition, and various core services, such as Cloud Identity, Gmail, and Calendar. You'll explore the functionality of each configuration, which will help you make informed decisions for your organization. Later chapters will show you how to implement security configurations that are available at different layers of Workspace and also how Workspace meets essential enterprise compliance needs. You'll gain a high-level overview of the core services available in Google Workspace, including Google Apps Script, AppSheet, and Google Cloud Platform. Finally, you'll explore the different tools Google offers when you're adopting Google Cloud and migrating your data from legacy mail servers or on-premises applications over to cloud servers. By the end of this Google Workspace book, you'll be able to successfully deploy Google Workspace, configure users, and migrate data, thereby helping with cloud adoption. What you will learn Manage and configure users in your organization's Workspace account Protect email messages from phishing attacks Explore how to restrict or allow certain Marketplace apps for your users Manage all endpoints connecting to Google Workspace Understand the differences between Marketplace apps and add-ons that access Drive data Manage devices to keep your organization's data secure Migrate to Google Workspace from existing enterprise collaboration tools Who this book is for This book is for admins as well as home users, business users, and power users looking to improve their efficiency while using Google Workspace. Basic knowledge of using Google Workspace services is assumed.